(untitled) (Dhaka University Journal of Science, 2023)
In this research work the non-linear refractive indices n2 was determined for the pure SnO2 and TiO2 doped SnO2 thin films by using the Z-scan technique. We have used a continuous wave Ar-ion laser with incident wavelength of 514 nm as the source. n2 was measured by varying three quantities: the incident laser intensity, thickness of the pure SnO2 films and doping concentration of TiO2 in SnO2 films. From the experimental results, the values of n2 were found to be increasing with the increase of thickness of the pure SnO2 films and also with the increase of doping concentration of TiO2 in SnO2 thin films. Dhaka Univ. J. Sci. 71(2): 104-110, 2023 (July)